2001
DOI: 10.1111/j.1471-0528.2001.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Can obstetric complications explain the high levels of obstetric interventions and maternity service use among older women? A retrospective analysis of routinely collected data

Abstract: Objective To determine whether the higher levels of obstetric intervention and maternity service use among older women can be explained by obstetric complications. Design A retrospective analysis of routinely collected data from the Aberdeen Maternity and Neonatal Databank. Participants All residents of Aberdeen city district delivering singleton infants at the Maternity Hospital 1988Hospital -1997. Main outcome measures Odds ratios for each intervention in older maternal age groups compared with women aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
67
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 17 publications
11
67
2
1
Order By: Relevance
“…Few women visited specialist doctors to discuss existing health issues, such as blood pressure. Choosing hospitals and birth-care options was another way in which women prepared for pregnancy, and being aware of the increased risks associated with their age, they especially valued the availability of emergency services at hospitals 16 . Having become pregnant, women adopted a different range of health promoting activities in response to their concerns and needs in relation to their pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Few women visited specialist doctors to discuss existing health issues, such as blood pressure. Choosing hospitals and birth-care options was another way in which women prepared for pregnancy, and being aware of the increased risks associated with their age, they especially valued the availability of emergency services at hospitals 16 . Having become pregnant, women adopted a different range of health promoting activities in response to their concerns and needs in relation to their pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Bell et al (2001) found that age-related increased intervention rates were independent of maternal complications during pregnancy, complications during labour, a history of infertility, and other confounding factors. Age alone was not responsible for gestational hypertensive disorders, although chronic hypertension was found to be more common among women of advanced maternal age.…”
mentioning
confidence: 95%
See 3 more Smart Citations